2003
DOI: 10.1034/j.1600-0714.2003.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and topical corticosteroid treatment of oral lichen planus: a comparative study with long‐term follow‐up

Abstract: The most suitable corticosteroid therapy in the management of OLP is the topical therapy, which is easier and more cost-effective than the systemic therapy followed by topical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 28 publications
4
147
0
6
Order By: Relevance
“…In our study, complete remission was observed in 66.7% (n=10) and partial remission in 33.4% (n=5) of patients after eight weeks of treatment with prednisolone 40 mg/day along with tapered doses, which was more or less similar to the results reported by Carbone M et al [24] A double blind placebo controlled randomized clinical trial conducted by Saawar N et al [6] transformation (up to 0.2-2%) as compared to another forms. [25,26] Therefore, it may be presumed that lycopene and prednisolone may decrease the risk of malignant transformation in OLP.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, complete remission was observed in 66.7% (n=10) and partial remission in 33.4% (n=5) of patients after eight weeks of treatment with prednisolone 40 mg/day along with tapered doses, which was more or less similar to the results reported by Carbone M et al [24] A double blind placebo controlled randomized clinical trial conducted by Saawar N et al [6] transformation (up to 0.2-2%) as compared to another forms. [25,26] Therefore, it may be presumed that lycopene and prednisolone may decrease the risk of malignant transformation in OLP.…”
Section: Discussionsupporting
confidence: 81%
“…Carbone M et al [24] found 40.9% (n=9) of patient with complete remission and 50 % (n=11) patients with partial remission of OLP lesion in initial two months of treatment with prednisolone 50 mg/day along with tapered doses. In our study, complete remission was observed in 66.7% (n=10) and partial remission in 33.4% (n=5) of patients after eight weeks of treatment with prednisolone 40 mg/day along with tapered doses, which was more or less similar to the results reported by Carbone M et al [24] A double blind placebo controlled randomized clinical trial conducted by Saawar N et al [6] transformation (up to 0.2-2%) as compared to another forms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, clobetasol propionate appeared to be one of the most effective topical steroids, as in an adhesive base led to complete remission in 56-75% of patients [17][18][19]. Unfortunately, some patients are refractory to topical corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, no se han encontrado diferencias estadísticamente significativas, no debiéndose olvidar además los efectos secundarios que el tratamiento sistémico es capaz de provocar. El tratamiento sistémico debería reservarse para aquellos pacientes con un LPO recalcitrante, en forma erosiva o atrófica, en el que el tratamiento tó-pico no está haciendo efecto, o en el que la extensión sistémica del LPO complica su manejo tópico (45).…”
Section: Sistémicosunclassified